(untitled) (Journal of Philosophy Culture and Political Science, 2019)
Abstrcat. The article contains an attempt to substantiate a new, post-non-classical paradigm of social cognition, its fundamental need in the cognitive space of modern social processes. We are talking about social heterology, leveling homogeneous, metaphysical, classical attitudes of social and philosophical discourse. The purpose of the article is to identify the heterologous, fractal essence of being as a singular cobeing. To this end, a critical analysis was made of the works of European and Russian philosophers, their theoretical generalization, heuristic synthesis, methods of social synergy, as well as social heterology itself. Two approaches have been identified, two main research models of social being: ontological and heterologous. The ontological approach is associated with the obligatory correlation of the social being with a certain transcendental foundation. Heterological approach is associated with a view of society, in which it is differences, and not identity, that are its main attribute. Being is the being of singular existence. Being is co-being. A fundamental transition from ontic constructions of classical philosophy to directly ontological ones is necessary. The novelty of the study is that social heterology legitimizes the principle of uncertainty of social cognition. The author’s position is that only the heterologous dimension of another sociality will allow one to come closer to an adequate understanding of the contradictions of the social life of modern man not only from the cognitive perspective, but, first of all, from the practical point of view, in order to define humane social policy. Key words: metaphysics, being, fractal, ontology, gnoseology, heterogeneous, difference, co-being.